-3x+2-5x-7=4+2

Simple and best practice solution for -3x+2-5x-7=4+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+2-5x-7=4+2 equation:


Simplifying
-3x + 2 + -5x + -7 = 4 + 2

Reorder the terms:
2 + -7 + -3x + -5x = 4 + 2

Combine like terms: 2 + -7 = -5
-5 + -3x + -5x = 4 + 2

Combine like terms: -3x + -5x = -8x
-5 + -8x = 4 + 2

Combine like terms: 4 + 2 = 6
-5 + -8x = 6

Solving
-5 + -8x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -8x = 6 + 5

Combine like terms: -5 + 5 = 0
0 + -8x = 6 + 5
-8x = 6 + 5

Combine like terms: 6 + 5 = 11
-8x = 11

Divide each side by '-8'.
x = -1.375

Simplifying
x = -1.375

See similar equations:

| 6p-49=11p-79 | | 9p+146=8p | | 4x-207=9-5x | | 20x+15y=950 | | z^2+2zi-2=0 | | -9(t^2+13)(t^2-7)=0 | | 48x=4.176 | | -4+14-24=x | | 8v+80=17v-100 | | 3x-11=4x-11 | | 0.05x=0.0815 | | 46b-42b+9b+10b-21b-1=39 | | 19c+45=31c-63 | | 5g+6kg=g | | (X*x)+((3x)*(3x))=(24*24) | | 10b-9b+7b+3b+1=45 | | 45h+11=34h+55 | | 12a-11a-a+11a+3=36 | | 7×1/2= | | (X-3)(x^2+4x+19)=0 | | 5g+6k=g | | 10x+5=2x-8x | | 15x^5-5/5x^4-10 | | 9q-5q+4q-6q-2=14 | | -4x^2-32x-48=0 | | (-3x-4y)(9x^2-12xy+16y^2)= | | I=1000-40(7) | | -2(3x+5)-2x=x-43 | | -4/11x=8/99 | | 2.25x+5=13.5t+14 | | 252=(4+y)16.8 | | 4(x+2)=4(x+13) |

Equations solver categories